The Liability of the Public Administration in the Peruvian Administrative Law: Approaches to an Institution Pending Reform - Sánchez Povis, Lucio Andrés (2015)
The author studies the protection that the liability of public administration regime offers against Public Administration’s actions in Peruvian Administrative Law. In this context, he notes the shortcomings of such regime and proposes Peruvian legislation must change in order to overcome this weakness. Finally, the author notes that it is necessary to change this regime in order to guarantee effective economic protection against illegal decisions of the Regulatory State.